Sensemaking, adaptation and agency in human-exoskeleton synchrony - Wilkenfeld, J. Nan; Kim, Sunwook; Upasani, Satyajit; Kirkwood, Gavin Lawrence; Dunbar, Norah E.; Srinivasan, Divya (Frontiers in Robotics and AI, 2023)
Introduction: Wearable I robots such as exoskeletons combine the strength and precision of intelligent machines with the adaptability and creativity of human beings. Exoskeletons are unique in that humans interact with the technologies on both a physical and cognitive level, and as such, involve a complex, interdependent relationship between humans and robots. The aim of this paper was to explore the concepts of agency and adaptation as they relate to human-machine synchrony, as human users learned to operate a complex whole-body powered exoskeleton. Methods: Qualitative interviews were conducted with participants over multiple sessions in which they performed a range of basic functional tasks and simulated industrial tasks using a powered exoskeleton prototype, to understand their expectations of the human-technology partnership, any challenges that arose in their interaction with the device, and what strategies they used to resolve such challenges. Results: Analysis of the data revealed two overarching themes: 1) Participants faced physical, cognitive, and affective challenges to synchronizing with the exoskeleton; and 2) they engaged in sensemaking strategies such as drawing analogies with known prior experiences and anthropomorphized the exoskeleton as a partner entity in order to adapt and address challenges. Discussion: This research is an important first step to understanding how humans make sense of and adapt to a powerful and complex wearable robot with which they must synchronize in order to perform tasks. Implications for our understanding of human and machine agency as well as bidirectional coadaptation principles are discussed.